Kemampuan Pemecahan Masalah Matematika: Sebuah Tinjauan terhadap Kepribadian Guardian dan Idealis - Rika Rika Arifah Sari; Fenny Anggreni; Mazlan Abduh (At-Tarbawi : Jurnal Pendidikan, Sosial dan Kebudayaan, 2021)
Classification of personality based on the MBTI personality grouped by David Keisey. The purpose of this study was to determine the differences in students' mathematical problem solving abilities in terms of guardian and idealistic personality types in SMA Negeri 4 vocational youth. This research is a qualitative research. The subjects of this study were 4 students from class X Mia 3 SMA Negeri 4. The data validity technique used in this research is triangulation technique. Data analysis techniques include, descriptive data of written test results and interview results, analyzed from written test results and interview results, then conclusions are drawn. The results of the discussion can be concluded that there are differences in mathematical problem solving abilities of guardian and idealist personality types. Guardian personality type subjects can fulfill all problem solving indicators according to polya, namely the stages of understanding the problem, planning solutions, solving problems, and re-examining and drawing conclusions properly and correctly, while subjects with idealistic personality types at the stage of understanding the problem do not write down what is asked. In the problem-solving stage there are errors so that the results obtained are wrong and do not meet one of the polya indicators, namely not re-examining the existing answers but can draw conclusions. So the researchers suggest that students can improve their mathematical problem solving skills well